The relationship between future goals and achievement goal orientations: An intrinsic-extrinsic motivation perspective - LEE, Jie Qi (Institutional Knowledge at Singapore Management University, 2018)
This research aimed to study the relationships between students’ future goals (FGs) and their immediate achievement goal orientations (AGOs) among 5733 Singaporean secondary school students (M age = 14.18, SD = 1.26; 53% boys). To this end, we hypothesized that the relationships between like valenced FGs and AGOs (both intrinsic or both extrinsic) will be stronger than those of opposite valenced FGs and AGOs (intrinsic–extrinsic) and tested two alternative models: Model A positing the prediction of AGOs by FGs and Model B positing the prediction of FGs by AGOs. Structural equation modeling showed the heuristic superiority of Model B in which intrinsic FGs (career-, society-, and family-oriented) were more strongly related to mastery-approach goal orientation than to performance-approach goal orientation and extrinsic FGs (fame- and wealth-oriented) were more strongly related to performance-approach goal orientation than to mastery-approach goal orientation. The findings suggest that, to enhance school motivation, teachers should encourage students to adopt intrinsic AGOs and FGs.